Surface characterization of sulfated zirconia and its catalytic activity for epoxidation reaction of castor oil. Issue 12 (2nd December 2019) - Yuan, Hong; Dong, Zhaoyang; He, Jie; Wang, Yunjie; Zhang, Hong
Abstract: The solid acid catalysts SO4 2− /ZrO2 were prepared by impregnation technique at different calcination temperatures. The surface characterizations were carried out by using scanning electron microscope (SEM), Fourier transform infrared spectrometer (FTIR), X-ray diffraction (XRD), temperature programed desorption of NH3 (NH3 -TPD), and N2 -BET. The SEM results showed that the size of the SO4 2− /ZrO2 was not uniform and varied from about 1 to 20 µm. The characteristic peaks in FTIR spectra were essentially the same within the calcination temperature range of 400–700 °C. The XRD results indicated that the transition temperature from amorphous to tetragonal phase was up to 500 °C. The strong acid and superacid sites of the samples could be observed by the NH3 -TPD results. The largest BET surface area was 140 m 2 /g, when the calcination temperature was at 500 °C, and all the pore size distributions belong to mesoporous range. The solid acid SO4 2− /ZrO2 was used for the epoxidation of castor oil. When the calcination temperature of SO4 2− /ZrO2 was 600 °C, reaction temperature 45 °C, and reaction time 8 h, the reaction effect was better with an iodine value of 33.0 ± 1.6 g/100 g and an epoxy value of 2.45 ± 0.11 mol/100 g.